Respuesta :

Simplifying
(6x + -5) + -1(7x + 2) = 0

Reorder the terms:
(-5 + 6x) + -1(7x + 2) = 0

Remove parenthesis around (-5 + 6x)
-5 + 6x + -1(7x + 2) = 0

Reorder the terms:
-5 + 6x + -1(2 + 7x) = 0
-5 + 6x + (2 * -1 + 7x * -1) = 0
-5 + 6x + (-2 + -7x) = 0

Reorder the terms:
-5 + -2 + 6x + -7x = 0

Combine like terms: -5 + -2 = -7
-7 + 6x + -7x = 0

Combine like terms: 6x + -7x = -1x
-7 + -1x = 0

Solving
-7 + -1x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + 7 + -1x = 0 + 7

Combine like terms: -7 + 7 = 0
0 + -1x = 0 + 7
-1x = 0 + 7

Combine like terms: 0 + 7 = 7
-1x = 7

Divide each side by '-1'.
x = -7

Simplifying
x = -7